A Time Series Approach to Examining Regional Economic Resiliency to Hurricanes. (April 2014) - Ewing, Bradley T.; Liang, Daan; Cui, Yuepeng
Abstract Hurricanes disrupt business processes and activities, energy distribution and consumption, and services of infrastructure and lead to a reallocation of resources and their uses. This research models the relationship among economic and engineering measures of the state of the built environment in order to provide insight into a region's ability to withstand and recover from a future hurricane. As such, we provide a quantitative approach to modeling and measuring a region's economic resiliency. The findings have implications for developing strategies for long‐term sustainability of economic regions.